Kako je propao rock and roll . The Fall of Rock and Roll - Gajić, Goran; Pezo, Zoran; Slavica, Vladimir (Avala Film Beograd ; FDU Beograd ; Maestro Film Zagreb, 1989)
Duration: 01:46:00 This comic omnibus consists of three independent stories about Belgrade youngsters in the late 1980s. The stories are interconnected through the character of Green Tooth, a comic book hero, who appears at the beginning of each story. In the first one named "Two paths to the brook" young Koma makes a bet that he will sell more records than his dad, a folk singer and a record company owner. With the help of his girlfriend he signs for his dad’s company as a mysterious ninja singer and eventually wins the bet. In the second part “Love isn’t everything, there is something in money too,” Dracula, guest at a costume party, seduces a young girl, but she doesn’t share his views of their future relationship. After he tries to avoid making any commitments, eventually he falls in love and she moves to his place. The final part, "Do not send me letters", focuses on a young couple – Eva and Đuro. One day an anonymous letter appears, apparently addressed to Eva and jealous Đuro does everything to find out who wrote it. When their homosexual neighbor is revealed as its sender, a happy end follows.